A descriptive epidemiology of substance use and substance use disorders in Nigeria during the early 21st century (2007)
Background: Several studies have examined the use of psychoactive substances among selected groups in Nigeria. Here, we extend the description to include the features of substance dependence. Method: A stratified multi-stage random sampling of households was used to select respondents in 21 of Nigeria's 36 states (representing 57% of the national population). In-person interviews with 6752 adults were conducted using the World Health Organization Composite International Diagnostic Interview, Version 3. Lifetime history and recent (past year) use, as well as features of dependence on, alcohol, tobacco, cannabis, sedatives, stimulants, and other drugs were assessed. Results: Alcohol was the most commonly used substance, with 56% (95% confidence interval, CI = 54, 58%) ever users and 14% (95% CI = 13, 15%) recent (past year) users, Roughly 3% were recent smokers (3%, 95% CI = 2.6, 4.2%). Next most common were sedatives. 4% (95% CI = 2.3, 4.5%), and cannabis smokers, 0.4% (95% CI =0.1, 0.6%). Males were more likely than females to be users of every drug group investigated, with male preponderance being particularly marked for cannabis. Prevalence of both alcohol and tobacco use was highest among middle aged adults. Moslems were much less likely to use alcohol than persons of other faiths, but no such association was found for tobacco, non-prescription drug use, or illegal drug use. Features of abuse and dependence were more common at the population level for alcohol; but among users, these features were just as likely to be experienced by alcohol users as they were by other drug users. Conclusion: Alcohol is the most commonly used psychoactive drug' in Nigeria. Features associated with drug dependence and abuse arc less prevalent but may require attention by public health authorities.